2019
DOI: 10.1177/0022034519830686
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Bacterial Biofilms in Dental Caries and Periodontal and Peri-implant Diseases: A Historical Perspective

Abstract: Over the last hundred years, groundbreaking research in oral microbiology has provided a broad and deep understanding about the oral microbiome, its interactions with our body, and how the community can affect our health, be protective, or lead to the development of dental diseases. During this exciting journey, hypotheses were proposed, and concepts were established, discarded, and later revisited from updated perspectives. Dental plaque, previously considered a polymicrobial community of unspecific pathogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
144
0
11

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(159 citation statements)
references
References 98 publications
(167 reference statements)
4
144
0
11
Order By: Relevance
“…Human periodontitis is a destructive form of periodontal disease that is triggered by pathogenic bacterial biofilms, possibly in synergy with certain lytic herpesviruses [1], and mediated by dysregulated host hyper-inflammatory responses, causing progressive connective tissue attachment loss and alveolar bone resorption around teeth, ultimately leading to their loss from the oral cavity [2]. Among the approximately 700 known microbial species and uncultivated phylotypes that inhabit the human oral cavity, only a subset is associated with a pathogenic subgingival microbial dysbiosis in periodontitis-affected patients [3]. Socransky et al [4], using DNA hybridization data, identified several clusters of bacteria as significantly related to various periodontal clinical conditions, with species belonging to the red and orange complex clusters most strongly associated with severe forms of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…Human periodontitis is a destructive form of periodontal disease that is triggered by pathogenic bacterial biofilms, possibly in synergy with certain lytic herpesviruses [1], and mediated by dysregulated host hyper-inflammatory responses, causing progressive connective tissue attachment loss and alveolar bone resorption around teeth, ultimately leading to their loss from the oral cavity [2]. Among the approximately 700 known microbial species and uncultivated phylotypes that inhabit the human oral cavity, only a subset is associated with a pathogenic subgingival microbial dysbiosis in periodontitis-affected patients [3]. Socransky et al [4], using DNA hybridization data, identified several clusters of bacteria as significantly related to various periodontal clinical conditions, with species belonging to the red and orange complex clusters most strongly associated with severe forms of periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…Particularly for dental caries, the microbial species are strongly associated with the metabolism of carbohydrates and develop acidogenic and aciduric environmental conditions. These species include Streptococcus mutans, Streptococcus sobrinus, Lactobacillus, Bifidumbacterium, and Scardovia species, among others [18][19][20]. Many successful protocols for prevention and control of dental caries and the different stages of periodontal disease have been implemented [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Current treatment available for peri‐implantitis is not satisfactory due to the lack of understanding of the disease pathogenesis . Some suggested that periodontitis and peri‐implantitis shares similar features associated with bacterial infection and the host immune responses, while others indicated that the two diseases show distinctive characteristics when compared with each other, although not all of them are human studies . ‒ Despite clinical data analysis and scientific reports, the mechanism of peri‐implantitis pathogenesis still remains unclear …”
Section: Introductionmentioning
confidence: 99%